2019
DOI: 10.3177/jnsv.65.541
|View full text |Cite
|
Sign up to set email alerts
|

Gastric and Jejunal Enteral Feeding Differently Affect Vitamin B<sub>12</sub> Status in Subjects with Severe Motor and Intellectual Disabilities

Abstract: The absorption of vitamin B12 is a complex process involving gastric acid and intrinsic factor as the indispensable components. In this study, we have investigated the effects of the administration site in enteral feeding on vitamin B 12 status in subjects with severe motor and intellectual disabilities (SMID). This is a cross-sectional study conducted from January to June 2016. Blood concentrations of vitamin B12, folate, vitamin B6, and homocysteine (Hcy) were measured in a total of 82 subjects (38 men, 44 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Another study showed that serum levels of folate and vitamin B6 are significantly higher in patients with severe motor or IDD using enteral feeding when compared to oral feeds. This study also demonstrated that among patients using enteral feeds, levels of B12 are significantly higher when using a gastrostomy tube compared to a jejunostomy tube [40]. However, gastrostomy tubes have been demonstrated to be inferior to jejunostomy tubes in prevention of aspiration pneumonia due to less likelihood of displacement or clogging [41].…”
Section: G-tubes/j-tubesmentioning
confidence: 61%
“…Another study showed that serum levels of folate and vitamin B6 are significantly higher in patients with severe motor or IDD using enteral feeding when compared to oral feeds. This study also demonstrated that among patients using enteral feeds, levels of B12 are significantly higher when using a gastrostomy tube compared to a jejunostomy tube [40]. However, gastrostomy tubes have been demonstrated to be inferior to jejunostomy tubes in prevention of aspiration pneumonia due to less likelihood of displacement or clogging [41].…”
Section: G-tubes/j-tubesmentioning
confidence: 61%